Faktor-Faktor yang mempengaruhi Penyerapan Tenaga Kerja pada Sektor UMKM di Indonesia: Pendekatan Error Correction Model - Azhari, A. (Fakultas Ekonomi Universitas Samudra, 2021)
The research aims to examine the short-term and long-term relationship of the MSMEs sector toward absorption employment in Indonesia. The method used is error correction model (ECM). The variables consisted of the number of MSMEs units, GDP and investment as independent variables, and MSME labor as the dependent variable. The data is used from 1996 to 2018. The results show that in the short term the number of MSMEs and GDP has a significant effect on employment in Indonesia; whereas only the number of MSMEs units will affect the employment of the MSME sector in Indonesia in the long run,. MSMEs are expected to increase their capacity in terms of business management. For policymakers and other stakeholders should to create programs in effort to increase the number of MSMEs as well as creating a conducive business climate for MSMEs players in Indonesia.